Energy storage capacitor preparation method and energy storage capacitor
By designing antiferroelectric nanodomain structures in energy storage capacitors and using PLD cavity depositing films, the problem of low energy density of energy storage capacitors is solved, and the effect of large energy storage density and high breakdown resistance is achieved.
Patent Information
- Application Number
- CN202411395688.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-03-07
AI Technical Summary
The energy density of existing energy storage capacitors is low, resulting in a larger volume and weight in the pulse power system, affecting system efficiency.
By designing the antiferroelectric nanodomain structure, the saturation polarization time is delayed, the strain stress of the antiferroelectric-ferroelectric phase transition is slowly released, the breakdown strength of the energy storage capacitor is improved, and the SrRuO3 and Pb0.97La0.02Zr1-xSnxO3 films are deposited using the PLD cavity to improve the energy storage density of the capacitor.
Energy storage capacitors with large energy storage density have been achieved, breakdown resistance is improved, and the volume and weight of the capacitor in the pulse power system are effectively reduced.
Smart Images

Figure CN119581219A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitors, and in particular to a method for preparing an energy storage capacitor and an energy storage capacitor. Background Art
[0002] In the development of clean energy, temporary energy storage has become an indispensable link. The current large-scale electrical energy storage technologies, such as large pumped power stations and compressed air, have been applied in the industrial field. With the advent of the mobile Internet era, the popularity of miniaturized portable electronic devices has greatly promoted the development of miniaturized power storage methods, such as batteries, electrochemical capacitors, dielectric capacitors, etc.
[0003] Compared with electrochemical capacitors and batteries, dielectric capacitors have ultra-high power density (10 8 W / kg) and ultra-fast charge-discharge capability (microseconds or even nanoseconds), and this energy conversion process is a physical process, without involving mass transfer and oxidation-reduction reactions, which can effectively avoid risks such as leakage and explosion, and is safer and more durable. Although dielectric energy storage capacitors have been widely used, they are limited by their small energy storage density. In general power electronics and pulse power systems, capacitors account for 23% and 40% of the total volume and weight, respectively. Therefore, the development of high energy density energy storage capacitors has become the current research focus in the field of pulse power technology. Summary of the invention
[0004] In order to solve the technical problem of low energy density of energy storage capacitors in the prior art, the embodiment of the present invention provides a method for preparing an energy storage capacitor and an energy storage capacitor. The technical solution is as follows:
[0005] In one aspect, a method for preparing an energy storage capacitor is provided, the method comprising:
[0006] A (001) oriented SrTiO3 (STO) substrate is attached to a heating support using silver glue, and then heated to a first temperature to cure the resin;
[0007] placing the heating support into the PLD cavity, extracting air from the PLD cavity to make the pressure in the PLD cavity lower than the first pressure, heating the PLD cavity to the second temperature, and adjusting the oxygen pressure to the first oxygen pressure;
[0008] SrRuO3 was deposited in an oxygen atmosphere for 2 min to 5 min;
[0009] The PLD chamber is cooled to the third temperature, the oxygen pressure is adjusted to the second oxygen pressure, and Pb 0.97 La 0.02 Zr 1-x Sn xO3 is used as the target for thin film deposition, where x is a real number between 0 and 1;
[0010] The pattern transfer of the top electrode is performed by photolithography, a layer of Pt is plated on the deposited film as the top electrode by magnetron sputtering, and the photoresist is removed by wet stripping.
[0011] Optionally, the first temperature is 150°C to 170°C.
[0012] Optionally, the second temperature is 680°C.
[0013] Optionally, the third temperature is 590°C.
[0014] Optionally, the thickness of the film after deposition is greater than or equal to 20 nm.
[0015] Optionally, after the thin film deposition, the method further comprises:
[0016] The temperature was lowered at a rate of 5 °C / min and in an oxygen atmosphere (1 × 10 4 Annealing treatment at 4000 Pa for 5-10 min.
[0017] Optionally, when PLZS is used as a target material for thin film deposition, the target-substrate distance is 60 mm.
[0018] Optionally, the first pressure is 10 -3 Pa.
[0019] Optionally, the first oxygen pressure is 13Pa, and the second oxygen pressure is 11Pa.
[0020] On the other hand, an energy storage capacitor is provided, and the energy storage capacitor is prepared by the method provided by an embodiment of the present invention.
[0021] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:
[0022] The embodiment of the present invention is to attach a (001) oriented SrTiO3 (STO) substrate to a heating tray with silver glue, and then heat it to a first temperature to solidify the resin; put the heating tray into a PLD cavity, extract the air in the PLD cavity, make the pressure in the PLD cavity below the first pressure, heat the PLD cavity to a second temperature, and adjust the oxygen pressure to the first oxygen pressure; deposit SrRuO3 (SRO) for 2-5 minutes in an oxygen atmosphere; cool the PLD cavity to a third temperature, adjust the oxygen pressure to the second oxygen pressure, and deposit Pb 0.97 La 0.02 Zr 1-x Sn xO3 is used as a target for thin film deposition, where x is a real number; the top electrode pattern is transferred by photolithography, a layer of Pt is plated on the deposited film by magnetron sputtering as the top electrode, and finally the photoresist is removed by wet stripping. The antiferroelectric nanodomain structure is designed to delay the saturation polarization time, so as to slowly release the strain stress of the antiferroelectric-ferroelectric phase transition, thereby improving the breakdown strength of the energy storage capacitor, and effectively generating a high energy storage density energy storage capacitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 is a flow chart of a method for preparing an energy storage capacitor provided by an embodiment of the present invention;
[0025] Figure 2 is a schematic structural diagram of a film provided by an embodiment of the present invention;
[0026] Figure 3 It is a schematic diagram of an electrical performance test structure provided by an embodiment of the present invention;
[0027] Figure 4 This is an XRD diagram of a PLZS antiferroelectric thin film provided by an embodiment of the present invention;
[0028] Figure 5 This is an AFM image of a PLZS antiferroelectric film provided by an embodiment of the present invention;
[0029] Figure 6 This is a diagram showing the relationship between polarization and time of a PLZS antiferroelectric thin film provided by an embodiment of the present invention;
[0030] Figure 7 This is a diagram showing the relationship between polarization and time of a PLZS antiferroelectric thin film provided by an embodiment of the present invention;
[0031] Figure 8 This is a transmission electron microscope image of a PLZS film provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0033] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0034] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they intend to express are the same. "of", "corresponding, relevant" and "corresponding" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they intend to express are the same.
[0035] In the embodiments of the present invention, sometimes a subscript such as W1 may be mistakenly written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are consistent.
[0036] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0037] According to the dielectric energy storage calculation formula: J reco =∫EdP, E and P are the electric field strength and polarization strength respectively. The energy storage density shows a positive correlation with both the electric field strength and the polarization strength. Improving the breakdown strength is an effective way to obtain a large energy storage density. Antiferroelectric materials exhibit their unique double hysteresis loops, which makes them have higher maximum polarization strength, lower residual polarization strength and higher energy storage density compared to the above three types of materials. They are even hailed as the most promising dielectric energy storage materials. There is still a big challenge for antiferroelectric energy storage materials: when antiferroelectrics are transformed into ferroelectrics under the action of an electric field, they are accompanied by huge stress and strain. Large strain and stress release are obviously not conducive to a large breakdown strength. As we all know, good insulation is the basic condition and important prerequisite for realizing dielectric energy storage. Under ideal conditions without considering dielectric adjustability or polarization saturation under high electric fields, the highest energy storage density and breakdown strength (E BDS ) is approximately proportional to the square of BDS The dielectric energy storage density can be significantly improved.
[0038] In order to solve the technical problem of low energy density of energy storage capacitors in the prior art, an embodiment of the present invention provides a method for preparing an energy storage capacitor and an energy storage capacitor.
[0039] On the one hand, a method for preparing an energy storage capacitor is provided, such as Figure 1 As shown, the method includes:
[0040] S1, attaching a (001) oriented SrTiO3 (STO) substrate to a heating support with silver glue, and then heating to a first temperature to cure the resin;
[0041] S2, placing the heating support into the PLD cavity, extracting air in the PLD cavity, making the pressure in the PLD cavity lower than the first pressure, heating the PLD cavity to the second temperature, and adjusting the oxygen pressure to the first oxygen pressure;
[0042] S3, depositing SrRuO3 (SRO) in an oxygen atmosphere for 2-5 min;
[0043] S4, cooling the PLD chamber to a third temperature, adjusting the oxygen pressure to a second oxygen pressure, and 0.97 La 0.02 Zr 1- x Sn x O3 (PLZS) is used as a target for thin film deposition, where x is a real number between 0 and 1;
[0044] S5. The pattern of the top electrode is transferred by photolithography, a layer of Pt is plated on the deposited film as the top electrode by magnetron sputtering, and the photoresist is removed by wet stripping.
[0045] The present invention is through La 3+ and Sn 4+ The doping of PbZrO3 breaks the orderly arrangement of dipoles in the antiferroelectric lead zirconate (PbZrO3, abbreviated as PZO) and obtains a relaxor antiferroelectric with a nanodomain structure (Pb 0.97 La 0.02 Zr 1-x Sn x O3, x=0, 0.15, 0.3, 0.45; abbreviated as PLZS#1, PLZS#2, PLZS#3, PLZS#4 respectively), so that the phase transition process of antiferroelectric PLZS is gradually relaxed, thereby improving the breakdown strength of the capacitor. Thereby improving the energy density of the energy storage capacitor.
[0046] In some embodiments, the thickness of Pt is 50 nm.
[0047] Optionally, the first temperature is 150°C to 170°C.
[0048] In some embodiments, the first temperature is 160°C.
[0049] Optionally, the second temperature is 680°C.
[0050] Optionally, the third temperature is 590°C.
[0051] Optionally, the thickness of the film after deposition is greater than or equal to 20 nm.
[0052] Optionally, after the thin film deposition, the method further comprises:
[0053] The temperature was lowered at a rate of 5°C / min and in an oxygen atmosphere (1×10 4 Annealing treatment at 4000 Pa for 5-10 min.
[0054] Optionally, when PLZS is used as a target material for thin film deposition, the target-substrate distance is 60 mm.
[0055] Optionally, the first pressure is 10 -3 Pa.
[0056] Optionally, the first oxygen pressure is 13Pa, and the second oxygen pressure is 11Pa.
[0057] The present invention is applicable to the pulsed laser deposition coating method. The pulsed laser deposition method used in the present invention is a physical vapor deposition technology for high-quality thin film epitaxial growth, which uses a laser to bombard a target material, deposits the bombarded plasma on a substrate, and realizes the epitaxial growth of the thin film. Compared with other antiferroelectric thin film preparation methods such as sol-gel method, chemical solution deposition method, atomic layer deposition method, etc., the pulsed laser deposition (PLD) system can perform uniform coating on composite materials with complex chemical compositions, and it is easy to ensure the stability of the stoichiometric ratio after coating, and can obtain a multi-component thin film with a desired stoichiometric ratio, that is, it has good composition retention characteristics.
[0058] In practical applications, energy storage capacitors can be prepared by the following methods:
[0059] 1. Preparation of thin film bottom electrode: stick the (001) oriented SrTiO3 (STO) substrate on the heating tray with silver glue, and then heat it to 150-170℃ and maintain it for 10 minutes to solidify the resin. Put the heating tray into the PLD cavity and evacuate it to 10 -3 Pa, then heat up to 680℃, adjust the oxygen pressure to 13Pa, and deposit SrRuO3 (SRO) for 2 min-5min in an oxygen atmosphere. In order to ensure the test of the electrical properties of the film, the thickness of SRO is required to be no less than 5nm.
[0060] 2. Antiferroelectric film epitaxial growth: The chamber temperature was lowered to 590°C, the oxygen pressure was adjusted to 11Pa, and the PLZS target was switched. The film growth parameters are shown in Table 1. Considering the size effect, in order to ensure the test of the electrical properties of the film, the thickness of the PLZS after deposition is required to be no less than 20nm. After the film is deposited, the temperature is lowered at a rate of 5°C / min and the target is placed in an oxygen atmosphere (1×10 4 The PLZS is doped with La 3+ and Sn 4+ .
[0061] Table 1 PLZS epitaxial film growth conditions
[0062]
[0063] 3. Preparation of top electrode: The pattern of the top electrode is transferred by photolithography, a layer of Pt is plated on the film as the top electrode by magnetron sputtering, and finally the photoresist is removed by wet stripping. The structure of the film is as follows Figure 2 As shown, the electrical performance test structure is as follows Figure 3 shown.
[0064] On the other hand, an energy storage capacitor is provided, and the energy storage capacitor is prepared by the method provided by an embodiment of the present invention.
[0065] The occurrence of electron breakdown is closely related to the bandgap width (Eg) of the material. When the electrons in the dielectric obtain high enough energy from the electric field and jump from the top of the valence band through the band gap between the valence band and the conduction band to the conduction band and repeat this process, the electrons will accumulate in the conduction band in large quantities, eventually leading to breakdown. The band gap of ideal dielectric materials is large, but the structure of actual dielectrics usually contains some defects such as missing atoms (vacancies) and foreign atoms (impurities). These defects will capture free electrons and form defect energy levels, causing Eg to decrease, making the material more susceptible to breakdown. The breakdown process of the dielectric and the size of the breakdown voltage depend not only on the performance of the dielectric itself, but also on the electric field distribution, temperature, heat dissipation conditions, and the properties of the surrounding medium. It is also affected by factors such as the pressure application speed and the duration of the voltage action.
[0066] There are many ways to improve the breakdown strength of capacitors, such as optimizing the synthesis process to improve density, interface engineering, constructing core-shell structures, introducing large bandgap materials, and "linear dielectric (or relaxor ferroelectric) + ferroelectric" composite structures. However, the above methods have a significant defect: the increase in breakdown strength is considered macroscopically, while the influence of large stress and strain effects caused by phase change during microscopic polarization is ignored. The patent of this invention proposes to delay the saturation polarization time by designing an antiferroelectric nanodomain structure to achieve the slow release of the strain stress of the antiferroelectric-ferroelectric phase transition, thereby enhancing the breakdown strength.
[0067] The energy storage capacitor prepared in the embodiment of the present invention is subjected to X-ray diffraction scanning of the deposited PLZS film sample, and the scanning modes are respectively θ-2θ scanning, such as Figure 4 As shown, sharp STO substrate peaks can be obtained, corresponding to the 001 and 002 diffraction planes of the substrate. Two diffraction peaks of the film appear at about 21.73° and 44.35°, respectively, and there are no other miscellaneous peaks. The diffraction peak of the bottom electrode SRO is shifted between the substrate peak and the film peak. The θ-2θ scan obtains the basic information of the out-of-plane structure of the film. According to the angles corresponding to these two peaks, the out-of-plane lattice constants of the PLZS film are calculated to be 4.08Å, 4.09Å, 4.16Å, and 4.16Å using the Bragg diffraction formula.
[0068] AFM was used to study the morphology and surface topography of the film to characterize the epitaxial growth mode and crystallinity of the epitaxial film. The AFM images show the surface topography plane of the epitaxial film ( Figure 5 As shown in Figure 1). The AFM image shows that the deposited epitaxial PLZS film has an atomically flat surface, with a minimum root mean square roughness Rq of 0.224 nm. This indicates that the film has good epitaxy and its growth mode is layered growth.
[0069] In order to intuitively demonstrate the gentle phase transition process of PLZS, the field-induced phase transition process is carried out by calculating the corresponding polarization as a function of the switching time. With the increase of Sn content, an obvious delayed phase transition process can be observed (e.g. Figure 6 As shown in Figure 2), we can clearly observe that the BDS The PLZS samples underwent a corresponding delayed saturation polarization process, and their electrical properties showed remarkable stability.
[0070] In order to evaluate the electric field tolerance of dielectric materials, a DC voltage is applied to the dielectric material until the sample breaks down, and the measured breakdown field strength of each sample is recorded. According to the experimental results, the following Weibull distribution function is used to fit the breakdown field strength of all components. The slope (β) of this linear fit is a shape parameter that can characterize the degree of discreteness of the dielectric breakdown strength of the sample. Figure 7 The figure shows the statistical distribution of the breakdown electric field of the PLZS series of films. It can be seen from the figure that with the increase of Sn content, the breakdown electric field will increase significantly, among which PLZS#4 shows the largest breakdown electric field.
[0071] In order to further characterize the structure of the film, the structure of the PLZS#4 film was studied using a spherical aberration-corrected transmission electron microscope. The HAADF-STEM image taken on the STO
[100] axis is shown in Figure 2. Figure 8As shown in the figure, it can be seen that there is a smooth surface interface between the epitaxial film, the SRO bottom electrode and the substrate, and the thickness of PLZS is about 220nm. Figure 8 The inset shows the selected area electron diffraction (SAED) of PLZS#4 film, from which we can find obvious superlattice diffraction spots (yellow arrows). This superlattice diffraction spot does not exist in ferroelectrics. It is mainly caused by the modulation structure of antiferroelectrics, which is an important feature of antiferroelectrics. By calculating the distance between the superlattice spot and the main spot and the ratio of the distance between the two main spots, it can be concluded that the modulation of antiferroelectrics (≈0.243) deviates from the modulation period (025) of classical antiferroelectrics. This is mainly because the element doping (La and Sn) has broken the long-range order of antiferroelectrics and disrupted their classical modulation period.
[0072] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0073] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0074] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0075] Those skilled in the art will appreciate that the units and algorithm steps of each example described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware, or a combination of computer software and electronic hardware. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professional and technical personnel can use different methods to implement the described functions for each specific application, but such implementation should not be considered to be beyond the scope of the present invention.
[0076] Those skilled in the art can clearly understand that, for the convenience and brevity of description, the specific working processes of the above-described equipment, devices and units can refer to the corresponding processes in the aforementioned method embodiments and will not be repeated here.
[0077] In the several embodiments provided by the present invention, it should be understood that the disclosed devices, apparatuses and methods can be implemented in other ways. For example, the device embodiments described above are only schematic. For example, the division of the units is only a logical function division. There may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another device, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be through some interfaces, indirect coupling or communication connection of devices or units, which can be electrical, mechanical or other forms.
[0078] The units described as separate components may or may not be physically separated, and the components shown as units may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the solution of this embodiment.
[0079] In addition, each functional unit in each embodiment of the present invention may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit.
[0080] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an energy storage capacitor, characterized in that: The method comprises: A (001) oriented SrTiO3 (STO) substrate is attached to a heating support using silver glue, and then heated to a first temperature to cure the resin; placing the heating support into the PLD cavity, extracting air from the PLD cavity to make the pressure in the PLD cavity lower than the first pressure, heating the PLD cavity to the second temperature, and adjusting the oxygen pressure to the first oxygen pressure; SrRuO3 was deposited in an oxygen atmosphere for 2 min to 5 min; The PLD chamber is cooled to the third temperature, the oxygen pressure is adjusted to the second oxygen pressure, and Pb 0.97 La 0.02 Zr 1-x Sn x O3 is used as the target for thin film deposition, where x is a real number between 0 and 1; The pattern transfer of the top electrode is performed by photolithography, a layer of Pt is plated on the deposited film as the top electrode by magnetron sputtering, and the photoresist is removed by wet stripping.
2. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The first temperature is 150°C to 170°C.
3. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The second temperature is 680°C.
4. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The third temperature is 590°C.
5. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The thickness of the film after deposition is greater than or equal to 20 nm.
6. The method for preparing an energy storage capacitor according to claim 1, characterized in that: After the thin film deposition, the method further comprises: The temperature was lowered at a rate of 5 °C / min and in an oxygen atmosphere (1 × 10 4 Annealing treatment at 4000 Pa for 5-10 min.
7. The method for preparing an energy storage capacitor according to claim 1, characterized in that: When PLZS is used as a target material for thin film deposition, the target-substrate distance is 60 mm.
8. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The first pressure is 10 -3 Pa.
9. The method for preparing an energy storage capacitor according to claim 1, characterized in that: The first oxygen pressure is 13Pa, and the second oxygen pressure is 11Pa.
10. An energy storage capacitor, characterized in that: The energy storage capacitor is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-energy storage density antiferroelectric thick membrane and preparation method thereof
CN108314443A
Preparation of AFE capacitor with high energy storage density and high energy storage efficiency, anti-ferroelectric film layer and preparation thereof and flexible AFE capacitor
CN112447413A
Anti-ferroelectric material, preparation method thereof and thin film capacitor
CN117986016A
Antiferroelectric multilayer ceramic capacitor
US20090207555A1
Cited By
Performance analysis method and system for metallized film flexible capacitor
CN120636635A